Taḥlīlu al Mufradāti al Dakhīlati min al Lughati al Injlīziyyati ilā al Lughati al ‘Arabiyyati fī Taṭbīqi Akhbāri al Taqniyyati wa al Tiknūlūjiyya: Dirāsatun fī ‘Ilmi al Dalālati - Mandaka, Dwi Arian Putra; Khasanah, Mushokhikhul (Al-Uslub: Journal of Arabic Linguistic and Literature, 2023)
In this thesis the author discusses the absorption vocabulary from English to Arabic in the technology contained in the application "Takniah Wa Taknulujia" (Studies in Dilalah Science), The object of this research is absorption vocabulary in technology. The type of research used is qualitative research, including library research or library research that takes data from the library. Data collection techniques used are reading techniques, choosing Arabic words/terms and analyzing data. And the purpose of this study is to find out the absorption vocabulary from English to Arabic in the technology contained in the "Takniah Wa Taknulujia" application and how the origin of the words in the "Takniah Wa Taknulujia" application and how the process of ta'rib occurs. The source of the research data is the application "Takniah Wa Taknulujia", then the method used to analyze the data is a description of the analysis.From the results of this study, there are 50 absorption vocabularies such as windows (ويندوز), plastation (بلايستشن) and others. In the application "At-Taqniah Wa Taknulujia" there are several forms of changes in the vocabulary of Ta'rib, namely changes in letters such as changing the letter "P" to the letter "ب ", besides that there is a change in harokat or vowels for example the letter "O" becomes dhomma or changes the letter "E" becomes kasroh, meanwhile there are also additions or subtractions of letters, for example in the Mobile sentence ((موبايل there is the addition of the letter alif before the letter "ي" and the addition of the letter "E" in the Mobile sentence.